Study of Quality and Quantity Asperula glomerata Essential Oil from Two Alborz Areas - Asghar Kohandel; Somayeh Ghasemi; Seyed Akbar Javadi; Reza Hajiaghaee (Institue of Medicinal Plants, ACECR, 2011)
Asperula glomerata, the plants belonging to value and range are protein classes in a three stage, active vegetative growth, flowering and seed respectively, is equal to 9/9, 10/1, 9/6. This plant also aspects of soil conservation are also important. In the treatment of diseases such as lowering blood pressure is use to reduce inflammation.   Asperula glomerata in 1389 in two stage, active vegetative growth and seed and two- week high in 1500-1700& >1900 m from the area Halejerd were collected. Aerial plant, including leaves, stems, flowers and seeds for three hours using distilled water extracts were measured with the device and aromatic compounds chromatograph device connected to the gas chromatography mass spectrometers were identified. This spuds aimed to determine the major compounds in the plant area was Halejerd. 375 total combined height of 1600m active growing phase, composition number 309 in the active growth phase height of 1900m, 372-phase composition and 270 combine the seed stage the height of 1600& 1900m week were identified. Rough extract total mass slurs and Alkan, fatty acid, steroid and was mono terpen. Oil compound in various stages of growth and height classes were different.